Spontaneous formation and closure of full thickness macular hole in a vitrecto-mised eye : a case report - Gurung, Rajya Laxmi (Nepalese Journal of Ophthalmology, 2018)
The exact pathogenesis of macular hole (MH) is controversial with most of the cases being idiopathic. Trauma is an important cause of secondary MH formation. MH post Pars Plana Vitrectomy (PPV) is an even rare entity with only a handful of cases reported so far ( Kumagai et al, 2008; Smiddy W.E, 1993; Kimura et al, 2005). An even rarer event is spontaneous closure of post PPV full thickness macular hole (FTMH), though spontaneous closure of traumatic macular hole (TMH) has been reported before. Herein, we report a 26 year old male patient who developed FTMH post PPV that closed spontaneously.